2018
DOI: 10.1186/s12944-018-0825-2
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-217 attenuates intima–media complex thickness of ascending aorta measured by ultrasound bio-microscopy and inhibits inflammation and lipid metabolism in atherosclerotic models of ApoE−/− mice

Abstract: BackgroundLittle investigation was done to test the efficiency of microRNA-217 (miR-217) on atherosclerosis in vivo.MethodsApoE−/− mice were used to construct atherosclerotic models and ultrasound bio-microscopy (UBM) was applied to detect the intima–media thickness (IMT) of the ascending aorta. The serum level of miR-217 and correlation with IMT was investigated. After miR-217 mimic administration, the IMT, inflammation, and lipid-associated molecules were assayed.ResultsThe serum level of miR-217 was reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Additionally, miR-126, miR-150, miR-155 and miR-142-3p have been demonstrated to serve critical roles in the development of atherosclerosis (39)(40)(41)(42). miR-217, which has been widely studied in cancer (15)(16)(17)(18), has been revealed to be upregulated in atherosclerosis (19,20). However, the role and molecular mechanism of miR-217 in atherosclerosis remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, miR-126, miR-150, miR-155 and miR-142-3p have been demonstrated to serve critical roles in the development of atherosclerosis (39)(40)(41)(42). miR-217, which has been widely studied in cancer (15)(16)(17)(18), has been revealed to be upregulated in atherosclerosis (19,20). However, the role and molecular mechanism of miR-217 in atherosclerosis remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA (miR)-217 has been studied in various types of cancer including liver cancer, gastric cancer, lung adenocarcinoma and acute myeloid leukemia (15)(16)(17)(18). Previous studies have revealed upregulation of miR-217 in atherosclerosis (19,20). However, whether miR-217 is involved in the development of atherosclerosis through the regulation of macrophages is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Further study showed that miR-125a, but not miR-455 inhibited expression of hepatic SR-BI in the mouse and rat livers as well as the mouse hepatic cell line Hepa 1-6 [176]. It was reported that miR-217 mimic administration in apoE-deficient mice significantly down-regulated SR-BI mRNA levels [177]. The mechanisms of miR-217-mediated regulation of SR-BI are not yet clear.…”
Section: Ncrnamentioning
confidence: 99%
“…However, it has also been reported that miR‐214 suppressed the activation of Ox‐LDL‐initiated autophagy and increased apoptosis in HUVECs . MiR‐34a and miR‐217 are pro‐atherosclerotic and anti‐angiogenic biomarkers that can induce senescence of endothelial cells by inhibiting the expression of SirT1 . As a functional marker in apoptosis, is recognized as a therapeutic target for atherosclerosis .…”
Section: Preclinical Studies Of Mirnas In Atherosclerosismentioning
confidence: 99%